Synthesis of Biodiesel from Soybean Oil with Methanol Catalyzed by Ni‐Doped CaO‐MgO Catalysts. Issue 37 (25th October 2019) - Pan, Langsheng; Xiang, Fuyun; Cheng, Zhipeng; Zhao, Xiaoyu; Fu, Lin; Li, Yongfei; Liu, Yuejin
Abstract: In order to improve the activity and stability of calcium‐based catalysts, a mixing method with other metal oxides was proposed to increase the interaction among the active ingredients to prevent the active components being leached off. A new Ni/CaO‐MgO catalyst was prepared by a double drop addition co‐precipitation method at alkaline condition around pH 10. The catalyst was characterized by XRD, TG‐TGA, FT‐IR, SEM, TEM, BET and CO2 ‐TPD. The results showed that Mg 2+ had been partly replaced by Ni 2+ which coordinated with oxygen octahedron to form strong basic sites at MgO defected lattices. The effect of different Ni addition on the catalytic performance was investigated in the transesterification reaction of renewable bio‐oils to biodiesel. Under the optimal reaction conditions of reaction temperature 120 °C, methanol/oil molar ratio of 27:1, catalyst dosage 5 wt%, the yield of biodiesel reached 97.6% only in 60 minutes of reaction time. Abstract : A new Ni/CaO‐MgO catalyst was prepared by a double drop addition co‐precipitation method at alkaline condition around pH 10. The results showed that Mg 2+ had been partly replaced by Ni 2+ which coordinated with oxygen octahedron to form strong basic sites at MgO defected lattices.